Early phenomenology and the origins of analytic philosophy - Soldati, Gianfranco; Bęben, Dariusz (Folia Philosophica, 2007)
The article sets the temporal and theoretical framework of early phenomenology, focusing on Brentano and Husserl, and outlines its shift from psychology to ontology as a pivotal stage leading to the emergence of analytic philosophy. The author emphasizes that both early phenomenology and analytic philosophy were characterized by a pronounced anti-psychologism, with the naturalistic form of anti-psychologism tracing directly back to Brentano’s and Husserl’s phenomenology, distinct from the later transcendental variant. The nineteenth-century debate on the relationship between philosophy and psychology is examined, from Kant’s critique of empirical psychology to Brentano’s descriptive psychology and the development of early phenomenology. In conclusion, Soldati argues that the naturalistic yet philosophical account of consciousness offered by early phenomenologists provided the foundational premises for the birth of analytic philosophy.